New product development success for vendors of automotive industry in Malaysia - Mohamed Suhaimi, Yusof (2021)
New Product Development (NPD) success can be defined as achieving a positive return on investment, the speedy introduction of products to market, improved product profit and quality, reduced cost of development, and improved in-house source ability and capability. The influence of production enhancements in the world, in ASEAN and especially in the Malaysian automotive industry, has prompted this study to investigate the NPD success for vendors of the automotive industry in Malaysia. Despite many challenges faced by the industry, minimal studies have been conducted to investigate the success of NPD among automotive vendors. Hence, this study intends to establish and examine the relationship between organizational factors and NPD success. Based on literature review, this research has identified four organizational factors that contribute to NPD success. The factors were information technology capability (IT capability), NPD strategy, NPD process and top management support (TMS). To test the framework of the study, a quantitative approach using questionnaire method was used. 175 questionnaires were distributed to vendors located in Malaysia. 90 questionnaires were returned and could be used for the analysis of data. The data obtained were analyzed using Structured Equation Modeling (SEM) using SmartPLS 3.2.4. The findings indicated that the NPD strategy, NPD process and TMS were significantly related to NPD success. In addition, the findings showed that TMS moderated the relationship between NPD strategy and NPD success. The results provide valuable insights to both practitioners and academia for further understanding of the NPD success. Outcome from this study will help managers, business professionals to justify further effort and investment in enhancing the knowledge, processes and infrastructure. By implementing this model, vendors can reduce the lead-time and costs, achieve customer satisfaction and sustain the business. Finally, the research limitations are discussed and suggestions on extended areas of research are outlined for future research.